The Uniform Dispute Resolution Policy - Meaning of the operative facts - Schneider, Dirk (Department of Commercial Law, 2014)
Aim of this work is merely to display the nature of the UDRP and to analyse the operative facts of the sec. 4 of the policy to find out the meaning of the terms used to make the result of the proceeding under the UDRP more predictable and more comprehensible. By doing so I will spot out some weak points and uncertainties in the policy and ambiguous interpretations by the panels. Therefore after an introduction dealing with the particularities of the Policy I will analyse decided and published cases with the focus on the findings dealing with the elements of sec. 4 (a) of the UDRP. Since the WIPO is the provider with the biggest amount of decided cases per year17, I will concentrate on its decisions.